US Nuclear Posture Reviews: A Comparative Analysis - Mr. Samran Ali (CISS Insight Journal, 2018)
The Nuclear Posture Review 2018 has generated a debate about the current US nuclear deterrence policy and its future scope vis-à-vis Russia and China. Some analysts term it a continuity of the previous reviews and others find it a departure from previous reviews. A closer look at the contents of 2018 and previous reviews helps clear this ambiguity of continuity or change. This paper examines the strategic environment, nuclear weapons role in the US defence and US stance pertaining to the arms control treaties in all Reviews. There are a few additional characteristics of the 2018 Review. US nuclear deterrence is made more credible by improving flexible response option and expanding the nuclear use scenarios. The review as well as US President Trump’s position on the arms control and disarmament may instigate an arms race between the US, Russia and China resulting in strategic instability globally.